The Role of Junta Islamica in the Rise of Moderate Muslims in Spain - Rofiq, Ahmad Choirul; Prahara, Erwin Yudi; Mashuri, Saepudin (Technium Social Sciences Journal, 2025)
This study examines the Junta Islamica’s role in promoting moderate Islam in Spain amid scarce research on Islamic organizations’ impact on da’wah and interfaith harmony in Al-Andalus. Founded in 1989, the organization uses education, halal certification, legal advocacy, interfaith dialogue, social integration, and media outreach to spread a message of moderation based on Qur’anic principles, defending Muslim civil rights, promoting gender equality, and rejecting extremism. It acts as a key civil society actor linking Muslims and the Spanish state, aided by constitutional freedoms and the legacy of convivencia, but faces challenges from Islamophobia, xenophobia, extremist violence, and far-right populism, notably from the Vox Party. The study presents the Junta Islamica as a model of peaceful, contextualized Islamic preaching that integrates faith, democracy, and human rights, advancing coexistence and civic inclusion in secular Spain.